Association of congenital abnormalities with maternal risk factors; an ultrasound based case-control study - Aslam Awan, Jawaria; Aisha; Ambreen; Samia (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the association between foetal congenital abnormalities and maternal risk factors, including family history and consanguinity. Method: The case-control study was conducted from December 2022 to May 2023 at the Radiology Department of Jinnah Postgraduate Medical Center, Karachi, and Tanveer Ultrasound Clinic, Karachi, after approval from the ethics review committee of Bahria University of Health Sciences, Karachi. The sample comprised pregnant women aged 18-40 years who were divided into foetuses with structural abnormalities group A and foetuses with normal structural development in control group B. Sonoscape S22 and Toshiba Aplio 500 ultrasound systems were used to detect congenital abnormalities. Maternal risk factors were assessed and associations were explored. Data was analysed using SPSS 23. Results: Of the 120 women, 60(50%) were in each of the two groups. Maternal age, family history of birth defects and a history of consanguinity were highly associated with an increased risk of congenital abnormalities (p<0.05). Diabetes mellitus, hypothyroidism and asthma had significant inverse associations with congenital abnormalities (p<0.05). Conclusion: Sociodemographic factors like age and risk factors played a significant role in the development of congenital abnormalities. Key Words: Congenital abnormalities, Risk factors, Consanguinity.